Quinidine in the treatment of KCNT1‐positive epilepsies. Issue 6 (18th November 2015) - Mikati, Mohamad A; Jiang, Yong‐hui; Carboni, Michael; Shashi, Vandana; Petrovski, Slave; Spillmann, Rebecca; Milligan, Carol J.; Li, Melody; Grefe, Annette; McConkie, Allyn; Berkovic, Samuel; Scheffer, Ingrid; et al.
Abstract : We report 2 patients with drug‐resistant epilepsy caused by KCNT1 mutations who were treated with quinidine. Both mutations manifested gain of function in vitro, showing increased current that was reduced by quinidine. One, who had epilepsy of infancy with migrating focal seizures, had 80% reduction in seizure frequency as recorded in seizure diaries, and partially validated by objective seizure evaluation on EEG. The other, who had a novel phenotype, with severe nocturnal focal and secondary generalized seizures starting in early childhood with developmental regression, did not improve. Although quinidine represents an encouraging opportunity for therapeutic benefits, our experience suggests caution in its application and supports the need to identify more targeted drugs for KCNT1 epilepsies. Ann Neurol 2015;78:995–999